Highly efficient thermally activated delayed fluorescence yellow organic light-emitting diodes with a low efficiency roll-off. Issue 26 (12th June 2019) - Li, Xiang-Long; Cai, Xinyi; Ali, Muhammad Umair; Su, Shi-Jian; Meng, Hong
Abstract : Highly efficient TADF yellow OLEDs with an extremely low efficiency roll-off have been obtained herein via rational device engineering. Abstract : A severe efficiency roll-off at high luminance in organic light-emitting diodes (OLEDs) generally results from a long exciton lifetime or an inappropriate device structure. The design strategy of the device plays a central role in realizing the inherent maximum potential of a specific emitter with an intrinsic photoluminescence quantum yield (PLQY) in an OLED via facilitating carrier injection, transport, and exciton confinement for efficient light emission. In this work, a yellow thermally activated delayed fluorescence (TADF) emitter, tri-PXZ-TRZ with a high PLQY and a short exciton lifetime is systematically investigated for its utilization in OLEDs. Judicious selection of suitable materials with higher energy offsets for the highest occupied molecular orbital (HOMO), the lowest unoccupied molecular orbital (LUMO) and triplet excitons as well as balanced carrier injection led to the realization of highly efficient OLEDs. The maximum external quantum efficiency (EQE) of the fabricated OLEDs with tri-PXZ-TRZ as the emitter is improved from 13.3% to 21.0% via rational device engineering. Upon achieving an effective balance between the efficiency and the corresponding roll-off, the EQE was found to be retained at >10% even at a super high luminance of 60 000 cd m −2 . Our results demonstrate that TADF emitter based OLEDs with well-designed device configurations could be promising for future low-cost and large-scale applications at high luminance.